Thyroid: Functional Food (Family Welfare, Family Physician, Nurse, Computational Validation, and Drug Discovery) - DEEPAK BHATTACHARYA (Jordan University of Science and Technology, 2023)
Goiter needs nursing. It is thyroid gland hypertrophy, important organ of endocrine system produces hormones for metabolism, poly organ normal function including blood chemistry, hemodynamics & erythropoiesis. Arising out of  Iodine deficiency and or life style, jointly or severally. Rarely cancer. Hypothalamus signals pituitary gland to produce thyroid-stimulating hormone (TSH), which regulates hormone production. TSH uptake and\or efficient conversion is the pathophysiology. Current standard medication for such pathophysiology  being long period ‘hormone replacement therapy’ (HRT). No prophylaxis; no synergic medicaments; no functional food. There are several natural sources (a) Star Anise -Illicium Verumtree (b) Cinnamon Bark - Cinnamon verum\cassia (c) Fruit & flower of  Myristica  fragrans are rich in (i) caffeic (ii) cinnamic acids; no conflicting and or confounding co-moieties; have abundant availability; historical (non-goiter specific) home use worldwide & non-toxic. Study indicates the theoretical-computational interaction of TSH with compound (i) & (ii). RESULT :   Binding affinity is of the order -5 kcal/Mol for either with a minimum of 4 ‘H’ bonds at ~ 2 Å distance and a stable-high ‘inhibition constant’ of   >180µm. Thus, compound (i) & (ii) present likeness, compatibility with TSH as Drug Discovery candidates at molecular level and also as ‘synergic’ with TSH.  Medicinal plant products  ‘A-B-C’ posits the immediate possibility of use as ‘Functional Foods’ targeting TSH uptake and\or efficient conversion. Goiter is chronic and is treated as  out-patient malady.  Caffeic & cinnamic acids rich functional foods are (A) prophylactic  (B) effective tools in the hands of the nurses. Paradigm shift in concept.